Characterization of the Two-Speed Subgenomes of Fusarium graminearum Reveals the Fast-Speed Subgenome Specialized for Adaption and Infection - Wang, Qinhu; Jiang, Cong; Wang, Chenfang; Chen, Changjun; Xu, Jin-Rong; Liu, Huiquan (Frontiers in Plant Science, 2017)
Fusarium head blight, caused by Fusarium graminearum, is one of the most severe diseases on wheat and barley worldwide. Although the genomic data of several strains were published, the intragenomic variation of F. graminearum was not well characterized. Here, We sequenced three Chinese strains and conducted genome-wide comparisons. Our data revealed that all the sequenced strains were distinct from each other and over 350 genes were functionally lost in each of them. Variants of each strain were unevenly distributed in a highly conserved pattern along the chromosomes, resulting in a conserved two-speed genome. The fast subgenome has a lower GC content, shorter gene length, and higher variation of exon numbers than the slow subgenome. Genes related to interaction and pathogenicity, under positive selection, and up-regulated in planta were all significantly enriched in the fast subgenome. Furthermore, we found that the fast subgenome coincided with facultative heterochromatin regions that were repressed in vegetative stage but activated during infection as measured by RNA-seq and ChIP-seq data, suggesting that the fast subgenome is epigenetically regulated. Taken together, our data demonstrated that F. graminearum has a highly conserved two-speed genome and the fast subgenome responsible for adaption and infection is under the control of heterochromatin.